PEMANFAATAN LEMPUNG DESA GEMA TERAKTIVASI H 2SO 4 UNTUK PENINGKATAN KUALITAS AIR GAMBUT - Vina Rotua; Akmal Muchtar; Halida Sophia (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The clay found in Gema Village, Kampar Regency, Riau Province contains many minerals, such as montmorillonite but it has a low surface area so need to do activation. The activator used in this study was H2SO4 0,5 M solution. The adsorbent was characterized by XRD, SEM and FT-IR. Activated Gema clay (LGT) and unactivated Gema clay (LGTT) were applied for purification a peat water using batch method with the variation of time 30, 60, 90 and 120 minute and several of water parameters were analized, such as odor, colour, pH, turbidity, TSS, TDS, concentrations of iron (Fe) and efficiency of decreasing of colour. All the results were compared to PERMENKES RI No. 416/MENKES/PER/IX/1990 “Tentang Syarat-Syarat Dan Pengawasan Kualitas Air”. Activated clay showed the refined morfology and increased which surface area from 10,5813 m2g-1 up to 15,3337 m2g-1. The result showed that the adsorption using activated Gema clay is better than unactivated Gema clay that is showed from removal efficiency percentage for all parameters. The longer of adsorption time, that was so many adsorbate that was adsorbed by adsorbent. The maximum time of adsorption was 120 minute. The removal efficiency percentage for pH, turbidity, TSS, TDS and efficiency of decreasing of colour were 10,03%, 30,98%, 58,59%, 59,28% and 30,84%, respectively for activated Gema clay (LGT). The statistic result showed that the variation of adsorption time affect all parameters that was analyzed based on the analysis of variance (ANOVA) and Duncan’s test at α = 0,05.